Journey to the unexplored world: an English Learner's L2 reader-response journals. (3rd July 2019) - Shin, Jaran
ABSTRACT: This study examines the reader-response journals of an English learner (EL) who read two works of historical fiction in his English Language Development class at a public high school in California. Locating this study within the tradition of research on reader response, it investigates how the EL constructs his own individualized meaning by reflecting on his personal history in interacting with the literature and how he reconciles multiple perspectives on the historical events described in the novels vis-à-vis his prior knowledge. The findings suggest that the journals written in English functioned as a window into the EL's experiences and as an avenue toward understanding various perspectives. The study exemplifies how reader-response journals, in conjunction with literary course materials, can facilitate the process of ELs' language learning and deepen the ways in which they view and read the world. Thus, reader-response journals serve as a cultivating force to help ELs constitute their identities as readers and to enhance their academic achievements.